Analisis Sengketa Kepulauan Senkaku : Perspektif Hukum Internasional dan Geopolitik Asia Timur - Diva Catur Widiyanto; Muchammad Fadhil; Restu Gesang Maulana; Mohammad Orlin Parusa; Loso Loso; Ganis Vitayanty Noor (Jurnal Hukum, Administrasi Publik dan Negara, 2025)
The Senkaku Islands dispute involves Japan, China, and Taiwan on the basis of historical claims, international law, and strategic and economic interests. The strategic value of this region increases along with the potential of natural resources and the importance of maritime routes in the East China Sea. The main problems in this research are, first, how is the chronology of the Senkaku Islands dispute, and second, how is the analysis of international law on the sovereignty claims of each party. This research uses a qualitative approach with a descriptive-analytical method, which is based on a literature study of international legal documents, scientific journals, and various related official sources. The results show that Japan controls the Senkaku Islands de facto and strengthens its claim based on the principle of effectiveness. In contrast, China and Taiwan make claims based on the history of the Ming and Qing Dynasties but have no actual control over the territory. The dispute is further complicated by the United States' security support for Japan, as well as increased maritime and military patrol activities around the disputed area. Efforts to resolve the dispute through the International Court of Justice have been stymied by Japan's refusal to recognize the dispute and China's caution in taking the case to international law. Overall, the dispute has not only a legal dimension, but also reflects the sharp geopolitical competition in the East Asian region. Resolving this dispute requires a flexible diplomatic approach, given that formal legal channels are difficult to pursue. Multilateral dialog is the key to preventing conflict escalation that could threaten regional stability.